Screening rate for Hepatitis D in Hepatitis B patients: Tips and tricks. (March 2023) - Costa, E. Garlatti; Da Re, M.; Villalta, D.
Abstract : Introduction: Hepatitis B virus (HBV) and its satellite virus hepatitis D (HDV) are common worldwide hepatotrophic infections responsible for cirrhosis and hepatocellular carcinoma. EASL practice guidelines recommend HDV screening in all Hep B patients. Novel therapies for Hep D are promising. Aim: To determine screening rates for HDV in HBV patients referred to our Laboratory of Hub Hospital Pordenone (Friuli Venezia Giulia). Methods: We retrospectively considered HBsAg positive results from 01.01.2018 to 31.12.2021. Using an extended database to 30.11.2022, we considered, among those were HBsAg positive, anti-HDV results and if we detected positivity for anti-HDV, we checked if HDV-RNA was performed. Results: 931 patients (55% non-Italian native) positive for hepatitis B surface antigen were studied with a majority male patients (65%). Of 931, 470 (50%) Hep B patients were screened for Hep D and 13 (1.4%) (9 non-Italian native) were positive for anti-HDV. Of 13, 6 were positive for serum HDV-RNA; 3 subjects were negative for HDV-RNA while 4 patients did not perform HDV-RNA. 10 Hep-B patients (1%) negative for anti-HDV at first time were re-tested for anti-HDV more than once. Comparing 2018-2019 vs 2020-2021, screening rate for Hep D decreased from 56% to 40%. Conclusions: Despite current HDV guidelines, in our Hospital HDV screening is suboptimal and it is actually declining. In fact COVID-19 has caused the slowing down of hepatitis testing program. Therefore we suggest: 1) anti-HDV simplified and automated reflex testing algorithms in Hep B patients for an early diagnosis and linkage to care of HDV infection; 2) enhancement of molecular biology for HDV-RNA assay in our Italian Labs; 3) repeating more than once anti-HDV especially in high-risk HBV patients. Furthermore, we need to be careful for Hep B vaccine to reduce Hep D screening and disease burden.